2020
DOI: 10.3390/ani10122245
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Oral Microbiome in Donkeys and the Effect of Dental Care on Oral Microbial Composition

Abstract: The objective of this study was to investigate the oral microbial composition of the donkey and whether basic dental treatment, such as dental floating, would make a difference to the oral microbial environment in donkeys with dental diseases using high-throughput bacterial 16S rRNA gene sequencing. Oral swab samples were collected from 14 donkeys with various dental abnormalities on day 0 (before treatment) and day 20 (twenty days after treatment). It is the first report focusing on the oral microbiome in don… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 33 publications
(41 reference statements)
3
6
0
Order By: Relevance
“…The predominant phyla in the donkeys’ oral cavities were Firmicutes , Proteobacteria , Actinobacteriota , Bacteroidota , Fusobacteriota , and Patescibacteria . This is in agreement with the findings of Zhu et al [ 18 ], who investigated the influence of dental care on the oral microbiomes of donkeys. In addition, the oral bacteria in the donkey shared some similarities with those of humans and other animals [ 25 , 26 , 27 , 28 , 29 ].…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…The predominant phyla in the donkeys’ oral cavities were Firmicutes , Proteobacteria , Actinobacteriota , Bacteroidota , Fusobacteriota , and Patescibacteria . This is in agreement with the findings of Zhu et al [ 18 ], who investigated the influence of dental care on the oral microbiomes of donkeys. In addition, the oral bacteria in the donkey shared some similarities with those of humans and other animals [ 25 , 26 , 27 , 28 , 29 ].…”
Section: Discussionsupporting
confidence: 93%
“…At the genus level, the predominant genera detected in the present study were Gemella , Streptococcus , Alysiella , etc. Zhu et al [ 18 ] also reported that the Gemella spp. and Streptococcus spp.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, the mouth and rumen, two complex and distinct microbial ecosystems, communicate in a bidirectional way. Comparison of the oral bacterial microbiota in different mammalian species tends to reveal extensive general similarity (Sturgeon et al, 2014;Gao et al, 2016;Ruparell et al, 2020;Zhu et al, 2020), although the species present in the microbiomes are different and often host-specific because of long-term co-evolution (Dethlefsen et al, 2007;Moeller et al, 2016). However, oral microbiomes are dynamic, with complex physiological and genetic interactions (Killian, 2018), and their association or correlation with health and disease is not limited to periodontal disease (Hajishengallis, 2015).…”
Section: Introductionmentioning
confidence: 99%